2020
DOI: 10.15295/bmij.v8i4.1526
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS OF THE RELATIONSHIP BETWEEN MACROECONOMIC VARIABLES and BIST-30 STOCK RETURNS

Abstract: In addition to the fundamental macroeconomic indicators such as inflation and interest rate which are very important for foreign investors, the Credit Default Swap (CDS), that shows the credit risk level of the country, is an important research topic. Therefore, in this study, it is aimed to examine the effects of Turkey CDS and selected macroeconomic variables on the Istanbul Stock Exchange (ISE) 30 index (XU30). For this purpose, Granger Causality Relations, Impulse-Response Charts and Variance decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
1
2
1
Order By: Relevance
“…The cointegration tests revealed cointegration relationships, that is, a long-term equilibrium relationship, between both the BIST-30 index and the Participation-30 index and the variables of the CDS premium and the VIX index for both pre-COVID-19 pandemic period and the pandemic period. This result is consistent with the existing studies in the literature that found out cointegration relation between, for example, the BIST-30 and the CDS premium (Kılcı, 2017;Noorie et al, 2020), and between the Participation-30 and the VIX index (İlgin, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The cointegration tests revealed cointegration relationships, that is, a long-term equilibrium relationship, between both the BIST-30 index and the Participation-30 index and the variables of the CDS premium and the VIX index for both pre-COVID-19 pandemic period and the pandemic period. This result is consistent with the existing studies in the literature that found out cointegration relation between, for example, the BIST-30 and the CDS premium (Kılcı, 2017;Noorie et al, 2020), and between the Participation-30 and the VIX index (İlgin, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Focusing on the CDS premium and the BIST-30 index, Kılcı (2017) found a cointegration relationship by using Engle-Granger cointegration test. Koy (2015) determined, based on Impact-Response graphs, mutual interaction while Variance Decomposition test by Noorie et al (2020) indicated a negative relationship between the same variables. On the other hand, Essayem et al (2022), found a negative relationship between the CDS premium and the Participation-30 index using the quantile regression method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The direction of causality does not change from the second week of March 2020 to the end of the sample period during the COVID-19 pandemic, indicating that the movements in CDS spreads are influential factors in predicting future stock prices in Turkey. The results contradict Gök (2020) and Noorie et al (2020), who do not find any significant evidence of causality.…”
Section: Gsadf Test Resultscontrasting
confidence: 80%
“…In another noteworthy empirical study, Gök and Çankal (2020) examined the bondstock market relationship at the aggregate and sectoral levels and found that both market returns were significant predictors of each other in the medium and long time horizons and there was a one-way causality from the negative shocks in stock prices to the positive shocks in interest rates. No causality, however, was found by Noorie et al (2020) among stock, CDS, and bond markets in Turkey. Hassan et al (2017), on the other hand, investigated the CDS-currency market relationship in Turkey employing both the rolling window causality and the Markov Switching VAR methods during the period 2009-2015.…”
Section: Introductionmentioning
confidence: 88%